2021
DOI: 10.3389/fphys.2020.621198
|View full text |Cite
|
Sign up to set email alerts
|

Program of Seven 45-min Dry Immersion Sessions Improves Choice Reaction Time in Parkinson’s Disease

Abstract: The study hypothesis held that in subjects with Parkinson’s disease (PD), the reaction time (RT) tests of the higher cognition demand would have more readily improved under the program of analog microgravity (μG) modeled with “dry” immersion (DI). To test this hypothesis, 10 subjects with PD have passed through a program of seven DI sessions (each 45 min long) within 25–30 days, with overall μG dose 5 1/4 h. Five patients were enrolled as controls, without DI (noDI group). Simple RT (SRT), disjunctive RT (DRT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Earlier we have shown that ground-based microgravity modeled with a short-term session of DI diminished tremor and muscle rigidity in Parkinson's disease (PD; Meigal et al, 2018Meigal et al, , 2021aMiroshnichenko et al, 2018), which can be attributed to the well-established atonia-inducing effect of DI on the skeletal muscle of healthy subjects (Navasiolava et al, 2011;Amirova et al, 2020). Additionally, the performance of the visual-motor reaction time tasks with higher cognition demand has improved after a program of DI sessions (Meigal et al, 2021b). However, these positive effects do not translate to quality of life and activity of daily living, or body balance (Meigal et al, 2018(Meigal et al, , 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we have shown that ground-based microgravity modeled with a short-term session of DI diminished tremor and muscle rigidity in Parkinson's disease (PD; Meigal et al, 2018Meigal et al, , 2021aMiroshnichenko et al, 2018), which can be attributed to the well-established atonia-inducing effect of DI on the skeletal muscle of healthy subjects (Navasiolava et al, 2011;Amirova et al, 2020). Additionally, the performance of the visual-motor reaction time tasks with higher cognition demand has improved after a program of DI sessions (Meigal et al, 2021b). However, these positive effects do not translate to quality of life and activity of daily living, or body balance (Meigal et al, 2018(Meigal et al, , 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Their anthropometric and clinical data and the medication they use is presented in Table 1 . All of them are from the same cohort of subjects who participated in our earlier studies [ 7 , 8 , 9 , 10 ]. The data on gait characteristics presented in this article were obtained from these studies.…”
Section: Methodsmentioning
confidence: 99%
“…The on-Earth microgravity was modeled using the conditions of a “dry” immersion (DI). This method of DI has already been presented in detail in our earlier papers [ 7 , 8 , 9 , 10 ]. In brief, the condition of DI was created with the help of MEDSIM (Medical simulator of weightlessness, Center for Aerospace Medicine and Technology, IMBP, Moscow, Russia), which is housed in the Laboratory of Novel Methods in Physiology (Petrozavodsk State University).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations